STRUCTURAL AND FUNCTIONAL CHANGES IN THE LEFT VENTRICLE IN PATIENTS WITH Q-MYOCARDIAL INFARCTION ON A BACKGROUND OF NON-DIFFERENTIATED DYSPLASIA OF CONNECTIVE TISSUE: BIOCHEMICAL ASPECTS OF THE PROCESS - Chernykh, M. (World of Medicine and Biology, 2015)
Introduction. Non-differentiated dysplasia of connective tissue (NDCT) can act as one of the important parts of Q-myocardial infarction (Q-MI) pathogenesis, including direct influence to the aspects that determine the main directions of diagnostic and preventive measures in patients with acute forms of ischemic heart disease: development of left ventricular systolic and diastolic dysfunction, slowing of reparative fibrosis, formation of postinfarction heart aneurysm, rupture of the heart. Aim of study - to conduct a comparative analysis of the levels of aldosterone and indices of left ventricular systolic and diastolic function in patients with acute Q-IM on the background of NDCT. Materials and methods. The study involved 60 patients aged 36 to 84 years (mean age 58,08±1,37 years), with first diagnosed Q-MI admitted to in-patient department on the first day of the disease. Exclusion criterions were comorbid nosologies affecting the clinical features, course and development of Q-MI complications: hypertension, obesity (Quetelet index > 30 kg/m2), diabetes, other severe comorbidies (COPD, malignancies), idiopathic mitral valve prolapse, repeated Q-MI, usage of veroshpiron for 2 weeks prior to the survey. All patients was performed echocardiography, general clinical and biochemical examination (determination of serum aldosterone - ELISA method). All patients were divided into 2 groups using a specially designed questionnaire to identify NDCT stigmas based on M. J. Glesby phenotypic map. The main group included 30 patients with 6 or more NDCT stigmas (average - 8,03±0,38), the comparison group - 30 patients with a number of stigmas NDCT up to 5 (the average - 4,42±0,13). Patients of both groups were representative by age, gender affiliation, localization of MI. Results. The analysis of left ventricular diastolic function (LVDF) in the studied groups found people with Q-IM on the background of NDCT had a significant increase in the ratio of the transmitral flows doppler velocity - E/A: 1,630±0,109, and for the group of patients without NDCT it was 1,139±0.104. Furthermore, a statistically significant difference established in average ejection fraction between patients of the main group (42,47±1,47) and a comparison group (49,77±1,64). Patients of the main group statistically significantly more frequently had grade II left ventricular diastolic dysfunction (LVDD) (pseudonormalisation) than the comparison group people. The level of aldosterone was higher in 18 patients (60%) of the main group against 2 patients (7%) of comparison group. The average level of aldosterone in main group patients was higher than normal and made up 179,86±19,21 pg/ml, while the comparison group - 67,14±14,31 pg/ml, which established a statistically significant difference. Grade II LVDD in patients with elevated levels of aldosterone and with NDCT found in 14 patients (47%). And 2 patients (7%) of the main group with the highest levels of aldosterone had grade III LVDD. A strong direct correlation found between aldosterone levels and E/A ratio in the main group of patients (r=+0,732; p